2009
DOI: 10.1091/mbc.e08-09-0971
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-14 Family Proteins HSET/XCTK2 Control Spindle Length by Cross-Linking and Sliding Microtubules

Abstract: Kinesin-14 family proteins are minus-end directed motors that cross-link microtubules and play key roles during spindle assembly. We showed previously that the Xenopus Kinesin-14 XCTK2 is regulated by Ran via the association of a bipartite NLS in the tail of XCTK2 with importin ␣/␤, which regulates its ability to cross-link microtubules during spindle formation. Here we show that mutation of the nuclear localization signal (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
201
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(224 citation statements)
references
References 68 publications
17
201
2
Order By: Relevance
“…Compared with CENP-E, Kid is a fast, but low processive motor 26 , which is probably why it works irrespective of microtubule stability. In a previous study, it was reported that chromosome alignment in cells depleted of Nuf2, a component of the Ndc80 complex, was significantly restored by co-depletion of HSET 2 , a minus-end-directed motor belonging to the kinesin-14 family 27,28 . We confirmed that the kinetochore to spindle equator distance was decreased by co-depletion of HSET in Hec1-depleted cells (Fig.…”
Section: Article Nature Communicationsmentioning
confidence: 97%
“…Compared with CENP-E, Kid is a fast, but low processive motor 26 , which is probably why it works irrespective of microtubule stability. In a previous study, it was reported that chromosome alignment in cells depleted of Nuf2, a component of the Ndc80 complex, was significantly restored by co-depletion of HSET 2 , a minus-end-directed motor belonging to the kinesin-14 family 27,28 . We confirmed that the kinetochore to spindle equator distance was decreased by co-depletion of HSET in Hec1-depleted cells (Fig.…”
Section: Article Nature Communicationsmentioning
confidence: 97%
“…Human HSET localizes between microtubules within the mitotic spindle. 93,94 HSET inhibition has no significant impact on bipolar anaphase or cell viability in human BJ fibroblasts, which exhibit virtually no centrosome amplification (B1%), 95 as well as mouse NIH-3T3 fibroblast and human MCF-7 breast cancer cells, which exhibit only 'low-level' centrosome amplification. 6 However, in cells with a higher incidence of centrosome amplification, such as isogenic tetraploids of the aforementioned cell lines or MDA-MB-231 cells, bipolar anaphase is inhibited and viability compromised by HSET knockdown.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 98%
“…96 Although HSET knockdown in HeLa cells does result in a minor attenuation of spindle pole focusing, central spindle stability, and microtubule density, along with a mild augmentation of spindle breadth, the occurrence of a bipolar anaphase remains unimpeded. 94 (ii) Astral microtubules are captured at kinetochores by the Ndc80 complex, thus forming kinetochore microtubules. Low-tension attachments activate the SAC, which provides time to correct the errors.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 99%
“…8d the hyperboloid model function with all three parameters isolated, where again the data points combine to collapse to the model surface. The reasons behind the exceptional behavior in Tobacco BY-2 cells and mouse oocytes (MI) are unknown, but we speculate that it might be related with the fact that plants in general are more tolerant to aneuploidy (Matzke et al 2003), while propagation of aneuploidy in the germline is (Goshima et al 2005), and 1.5 (Reis et al 2009) 1.2 Human HeLa 13 16 0.9 SL-14.3 (Cai et al 2009), 12.5 c (Tokai-Nishizumi et al 2005 and 12 (Jorge Ferreira, personal communication); MD-9 d (Meraldi et al 2004), 23.5 (Zhao et al 2008, 17 (Arnaoutov et al 2005), 15.2 (Kallio et al 1998) and14 (Jorge Ferreira, personal communication);and F-0.9 (Amaro et al 2010) 2.2…”
Section: A Relation Between Flux Velocity Spindle Size and Metaphasementioning
confidence: 99%